2018
DOI: 10.1128/mra.00940-18
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Pseudomonas aeruginosa Multidrug-Resistant Clinical Isolates, PAL0.1 and PAL1.1

Abstract: Pseudomonas aeruginosa infections are challenging due to intrinsic and acquired resistance mechanisms. We report here the draft genome sequences of two multidrug-resistant strains—PAL0.1, isolated from the airways of an intensive care unit (ICU) patient with ventilator-associated pneumonia, and PAL1.1, isolated from blood cultures of an ICU patient with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Several published studies on P . aeruginosa genome characterization have highlighted the prevalence of blaPAO and blaOXA50 which are classified as β-lactamases resistance genes [ 44 , 45 ]; and this does not make a difference in the P . aeruginosa strains under study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several published studies on P . aeruginosa genome characterization have highlighted the prevalence of blaPAO and blaOXA50 which are classified as β-lactamases resistance genes [ 44 , 45 ]; and this does not make a difference in the P . aeruginosa strains under study.…”
Section: Discussionmentioning
confidence: 99%
“…The aph(3’)-IIb variant found in both UY1PASBAL and UY1PSABAL2 genome has been observed among MDR P . aeruginosa from several studies [ 44 , 45 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before, the resistome analysis revealed that the five isolates harbored the beta-lactamase genes bla OXA-396 and bla PAO . Previous studies demonstrated the high prevalence of these genes in P. aeruginosa isolates from different sources and their contribution to antimicrobial resistance in this species [ 23 , 24 , 25 , 26 , 27 ]. According to the ResFinder tool on WGS from the five CF isolates, no carbapenemase genes were detected.…”
Section: Resultsmentioning
confidence: 99%